Towards optimization methods for movelets extraction in multiple aspect trajectory classification - Portela, Tarlis Tortelli (2023)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2023.